Mercury-Induced Chromosomal Damage in Wild Fish (Dicentrarchus labrax L.) Reflecting Aquatic Contamination in Contrasting Seasons - Mohmood, I.
Ria de Aveiro (mainly Laranjo basin, Portugal) has been subjected to mercury contamination from a chlor-alkali plant, currently presenting a well-described mercury gradient. This study aimed to assess mercury genotoxicity in this area by measuring the frequency of erythrocytic nuclear abnormalities (ENA) in the European sea bass (Dicentrarchus labrax), addressing the relation with total mercury concentration in the blood and the modulatory role of seasonal variables. Fish were collected, in warm and cold periods, at three locations differing in their distances to the main mercury source: reference (R), moderately (M), and highly (H) contaminated sites. Genotoxicity was detected in both degrees of contamination (M and H) and in both periods of the year (warm and cold), which is in line with the greater levels of mercury measured in fish blood. No significant seasonal variations were observed for mercury bioaccumulation or ENA frequency. The apparent low imperviousness of ENA frequency to seasonal factors reinforced its consistency as a genotoxicity biomarker, thus enabling a clearer identification of cause-and-effect relationships. Overall, the results reflected a serious environmental risk to native ichthyofauna at Laranjo basin due to mercury contamination, showing a potential of mercury to induce genetic damage in fish blood cells through clastogenic and/or aneugenic actions.